Art, History and Material Culture. A Study of Mesopotamic Cylinder Seals - Paim Pozzer, Katia Maria (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
The research project Art, History and Material Culture - a Study of Mesopotamian Cylinders Seals is developed by the Laboratório de Estudos de Antiguidade Oriental (LEAO), at the Universidade Federal do Rio Grande do Sul (UFRGS - Brazil), during the triennium 2018-2020. A short description of it is presented here.